GE_GERICHTE P/456/2012 vom 25. November 2013 - GE Cour de justice (2013)
AGRESSION; LÉSION CORPORELLE SIMPLE; CONCOURS D'INFRACTIONS; FIXATION DE LA PEINE; DÉPENS; PLAIGNANT | CP.134; CP.123; CP.47; CPP.433